Testing Different Strategies for the Remediation of Soils Polluted with Lindane - Salazar-Gonzalez, R; Vidal-Fuentes, J; Vidal-Fuentes, J (Elsevier B.V., 2020)
This work attempts to clarify the remediation processes involved in the treatment of soil spiked with non-soluble species like lindane. To achieve this goal, the remediation of spiked soil is evaluated coupling electro-kinetic soil flushing (EKSF) with three types of permeable reactive barriers (PRB) which consist of soil merged with nanoparticles of ZVI (n-ZVI), granular particles of ZVI (m-ZVI) or granular activated carbon (GAC). Likewise, the effect of reverse polarity in EKSF will be assessed. Results show that, for a given electric field applied, the intensity reached depends on the size and materials of the reactive particles contained in the PRB and decreases in the sequence EKAB-EKmZVIB-EKnZVIB. Additionally, water content and pH and conductivity profiles between rows of electrodes are also affected by the presence of PRB, mainly because ZVI particles can behave as bipolar electrodes and, thus amend current lines and water flux. In terms of lindane mobilization, the differences are even more remarkable since iron particles promote lindane dehalogenation and activated carbon shows a very good adsorption capacity for lindane. After 720 h of operation, the percentage of lindane extracted is below 2% in all EK-strategies while the percentage retained in soil depends on the strategy used: REKSF seems to prevent lindane removal while EKSF and EKAB lead to higher removal. Results are significant for the design of full-scale applications for the remediation of soils polluted with non-soluble species. © 2019 Elsevier B.V.